Evolving banking market structure in Oman: should CBO approve the mergers?. Issue 2 (30th April 2019) - Al-Muharrami, Saeed
Abstract : Purpose: In 2013-2014, Bank Muscat and National Bank of Oman requested a merger and Bank Sohar and Bank Dhofar lodged a similar request. This paper aims to investigate the shape of the market structure, and it tries to answer whether approving such requests is good for the industry, economy and society. Design/methodology/approach: The study examines the market structure of Oman Banking Industry, and it also presents the shape of the market structure if there had been an approval for these mergers' requests. The Herfindahl–Hirschman Index (HHI) and the biggest k-banks Concentration Ratio (CRk), which measure concentration changes over 17 years during the period 1998-2014, are used in this study. Findings: The study finds that Oman's Banking Industry is highly concentrated, which should cause concerns over these two requests of mergers or similar requests in the future. In general, the concentration ratio shows decreasing trend. The concentration ratio in the deposit market implies a concentrated market with CR2 and CR3 recording 67 and 85%, respectively, while HHI reached 2, 864 points in the 1998. However, in 2014, the concentration ratio had decreased, to CR2 and CR3 recording 52 and 65% respectively, and HHI standing at 2, 112 points. Research limitations/implications: The researcher suggests future investigation and further research in setting a benchmark index as a guideline for mergers' requests. Practical implications: Exercising monopoly power, by fewer banks, is very harmful to the economy. Charging higher interest rates on business loans escalates the cost of production of products and services which will cause inflation; therefore, monopoly power will lead to slow growth of the economy. Social implications: Regulators in Central Bank of Oman (CBO) or in any central bank should be very careful in granting mergers, especially among big banks, because it enables newly bigger banks to exercise monopoly power, thereby harming depositors who will be getting low deposit interest rates and harming borrowers by charging them high loan interest rate. Originality/value: Even though, this study discussed two requests of mergers between banks in Oman; however, it has presented formal approaches to the measurement of market structure in any country. Overall, it provides the policymakers in making the final decisions on mergers between banks in the future which are not limited to these banks or to Oman's Banking Industry.